The Relationship Between Mobile Money And Fnancial Inclusion In Ghana: The Moderating Role Of Social Networks - Derland Joseph Otu (knust, 2025)
I Am Grateful To The Almighty God For His Grace And Mercy Throughout This Mba Journey. I Thank My Supervisor Dr Mireku Of Knust For His Patience And Guidance. Also, Mary Effah Otu For Her Massive Support, And Josemay Nana Akua Otu.